group guidance, image media, spe Group guidance using the storytelling method using series of picture media to improve the speaking skills of children aged 5-6 years at RA Nawira Aulia: Counseling Guidance Action Research - hanifah, alfina (Prodi Bimbingan dan Konseling universitas PGRI Semarang, 2025)
Alfina Hanifah “Group guidance using the storytelling method using series of picture media to improve the speaking skills of children aged 5-6 years at RA Nawira Aulia.